A Pilot Study on Determination of Dynamic Behavioral Characteristics by Soil Response Analyses: A Case concerning Üngüt District of Kahramanmaraş Province - Kübra Ceren; Eyyüb Karakan (Doğal Afetler ve Çevre Dergisi)
It is not possible to prevent the earthquakes and other natural disasters which cause loss of lives and property, but it is possible to minimize the damages that they cause. The majority of the surface area of Kahramanmaraş province, which can be considered a vulnerable zone in Turkish Tectonic System, underlies many active fault systems. Determination of engineering properties of soils is of great importance in determination of soil behavior and/or minimization of damages due to seismic action. For this reason, dynamic analyses were conducted in the Üngüt district of Kahramanmaraş and data obtained from 12 borings in Üngüt region were used in the analyses. In this scope, dynamic ground behavior analyses were performed on certain points in the study area by the use of Deepsoil software. Linear, frequency domain in the equivalent linear and time domain non-linear analysis have been carried out to obtain information about the dynamic behavior of the local soil conditions. Dynamic behavior analysis of the selected area was carried out using the acceleration recordings of the 17 August 1999 Kocaeli (Mw = 7.4) earthquake. As a result of the analyses, variation of acceleration, response spectrum and amplification factor were obtained. In this study, by evaluating the data obtained, it is aimed to determine the dynamic behavior of the foundations of the existing and new buildings.